2002
DOI: 10.1007/s00270-001-0064-0
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Magnetic Resonance Angiography MoBI-trak in the Study of Peripheral Vascular Disease

Abstract: Our work is in accordance with the literature. Using this technique MoBI-trak has been shown to be a reliable technique for the detection of peripheral vascular disease up to the trifurcation, although it underlines the necessity for more diagnostic investigation and improvements in the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24] To the best of our knowledge, only 2 small trials have focused on the accuracy of MRA as the sole method in therapy planning. Carriero et al 26 reported a sensitivity of 100% and a specificity of 97.1% for the detection of stenoses Ͼ70% in 11 patients, but 6 lesions were overestimated and 1 occlusion underestimat- Figure 1ࡗ Subtracted coronal MIP image of MRA (left) and DSA (right) from a patient with claudication in the right leg. Arrows mark the long-segment occlusion of the right SFA.…”
Section: Discussionmentioning
confidence: 95%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24] To the best of our knowledge, only 2 small trials have focused on the accuracy of MRA as the sole method in therapy planning. Carriero et al 26 reported a sensitivity of 100% and a specificity of 97.1% for the detection of stenoses Ͼ70% in 11 patients, but 6 lesions were overestimated and 1 occlusion underestimat- Figure 1ࡗ Subtracted coronal MIP image of MRA (left) and DSA (right) from a patient with claudication in the right leg. Arrows mark the long-segment occlusion of the right SFA.…”
Section: Discussionmentioning
confidence: 95%
“…However, the presence of a stent can alter the accuracy of these techniques (4, 5). The evaluation of vessels deeper in the body generally requires the use of digital subtraction angiography (32). Contrast‐enhanced MRI (CE‐MRI) has been shown to provide accurate information to assist the physician in determining whether there is a need for surgical treatment in the aorto‐iliac, femoral‐popliteal, and carotid arteries (33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…MR angiography using gadolinium-based contrast agents and multistation bolus chasing facilitates rapid and detailed assessment of the peripheral arteries. MR angiography does not require sedation, eliminates exposure to ionizing radiation and can accurately diagnose lower extremity vascular disease (2)(3)(4)(5)(6)(7). Indeed in many centers, gadolinium-enhanced MR (Gd-MR) angiography now forms the mainstay of peripheral arterial assessment, with DSA largely reserved for therapeutic rather than diagnostic interventions (2).…”
mentioning
confidence: 99%